Recognition criteria and application of lake eutrophication evaluation based on set pair analysis - Yuan, Shi man; Li, Fan xiu (International Journal of Scientific Research and Management (IJSRM), 2020)
The set pair analysis evaluation method has been applied to evaluate water quality. However, in real-life applications, because traditional assessing methods usually yield extreme results and are of poor resolution, a hybrid recognition criterion, entropy weight and set pair analysis model is established. The concepts and calculated methods of assessment grade fuzzy characteristic and confidence criterion were proposed in order to solve the problem of determination of the magnitude of lake eutrophication. And the weight value was calculated by entropy weight method and finally got the evaluation grade as a confidence interval based on confidence level. Compared with the set pair analysis based on triangular fuzzy number method (SPA(TFN)) and the improved set pair analysis method (ISPA), the evaluating results of this model are more reasonable and its resolving power is higher. This study offer new insights and possibility to carry out an efficient way for lake eutrophication status evaluation. The study also provides scientific reference in lake risk management for local and national governmental agencies.